Pengaruh Bauran Pemasaran Terhadap Perpindahan Merek Pelanggan Restoran Cepat Saji di Karawang Menggunakan Metode Markov Chains dan Game Theory - Rianita Puspa Sari; Ahmad Surahman; Aditia Ayu Rahma Nabila (JIEMS (Journal of Industrial Engineering and Management Systems), 2019)
As an area that has evolved into one of the industrial cities in Indonesia, Karawang has experienced rapid growth, especially in the fields of industry and business. This causes a change in lifestyle so that modern society is bornthat is synonymous with consumptive behavior patterns which result in new needs that are presented practically in people's lives, one of which is restaurant food needs so that growth presence of fast food restaurants in Karawang. Competition between fast food restaurants can result in the brands switch to customers, so marketing mix strategy (9P) is needed (Product, Price, Promotion, Place, People, Process, Physical Evidence, Packaging, Payment). This study aims to analyze the effect of the marketing mix on brand movement, the rate of movement of fast food restaurant brands (X, Y, and Z) at Karawang, and the right strategy for companies to win the competition. The Markov Chains method is used to predict the market share of a product from the level of transfer of fast-food restaurant brands in Karawang, while Game Theory is to determine the right strategy in the marketing mix in the face of shifting customer brands. Research results obtained from 113 respondents who are valid and reliable,with the relationship of the two low variables are negative at -0.083 interpreting that the marketing mix correlation with brand displacement has an inverse relationship so that the marketing mix of fast food restaurants increases, the customer's brand shift will be lower. The brand transfer rate is predicted to have a market share in the coming year of 33.2% X, 36.2% Y and 30.6% Z with competitive strategies that can be done by increasing the Promotion and Location of Fast Food Restaurants.